2015
DOI: 10.1186/s12936-015-0832-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mushroom Agaricus blazei on immune response and development of experimental cerebral malaria

Abstract: BackgroundCerebral malaria (CM) is debilitating and sometimes fatal. Disease severity has been associated with poor treatment access, therapeutic complexity and drug resistance and, thus, alternative therapies are increasingly necessary. In this study, the effect of the administration of Agaricus blazei, a mushroom of Brazilian origin in a model of CM caused by Plasmodium berghei, strain ANKA, was investigated in mice.MethodsC57BL/6 mice were pre-treated with aqueous extract or fractions of A. blazei, or chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 60 publications
1
13
0
3
Order By: Relevance
“…Here, we reported a notable decrease in parasitaemia levels in the first 8 days of infection in PbA-infected mice treated with Ext-Ts. In accordance, previous research found that C57BL/6 mice inoculated with 1 × 10 5 PbA-infected RBCs and treated with aqueous extract of the fungus Agaricus blazei also showed reduced parasitaemia and enhanced survival, this effect being associated with diminished expression of IL-1β, TNF and IL-6 in the brain 29 .…”
Section: Discussionsupporting
confidence: 91%
“…Here, we reported a notable decrease in parasitaemia levels in the first 8 days of infection in PbA-infected mice treated with Ext-Ts. In accordance, previous research found that C57BL/6 mice inoculated with 1 × 10 5 PbA-infected RBCs and treated with aqueous extract of the fungus Agaricus blazei also showed reduced parasitaemia and enhanced survival, this effect being associated with diminished expression of IL-1β, TNF and IL-6 in the brain 29 .…”
Section: Discussionsupporting
confidence: 91%
“…In another study, mice infected with Leishmania amazonensis, L. chagasi, and L. major showed a significant reduction in the number of parasites in different organs. Moreover, no side effects were observed and an enhanced effectiveness was attained compared to those by conventional drugs such as amphotericin B (VALADARES et al, 2011). The aqueous extract of A. blazei was also effective in the control of Plasmodium berghei in experimentally infected mice, thus, representing an alternative for the treatment of malaria (VAL et al, 2015).…”
Section: Introductionmentioning
confidence: 96%
“…52 As mentioned, AbM did improve cerebral inflammation from malaria. 47 Moreover, HE mycelium and HE-derived erinacine A protected against neural cell death induced by brain ischaemia in a rat model by inhibiting iNOS and MAP kinase, proinflammatory cytokines TNFα, IL-1β and IL-6, and promoting nerve growth properties. 53 In a randomized clinical study (RCT), multiple myeloma patients undergoing high-dose chemotherapy and given add-on placebo-controlled treatment with the AbMbased Andosan™ for 2 months, were found to have the following immunomodulatory effects 12 : Reduced IL-1ra levels in plasma and increased T regulatory cells indicating anti-inflammatory effect, and increased plasmacytoid DC in blood and increased expression of genes in bone marrow aspirate at end of study vs before for KIRs and MHC antigens, the latter being important for antigen presentation.…”
Section: Effects Of Abm He and Gfmentioning
confidence: 98%
“…instillation. 47 A GF furanone is found to inhibit opportunistic Pseudomonas sp. pathogens in a plaque formation test.…”
Section: Of Abm He and Gf Against Bacteria And Parasitesmentioning
confidence: 99%